Building construction illustrated / Francis D.K. Ching. - Ching, Francis D. K., 1943- (John Wiley & Sons, Inc., 2014)
"This new edition of the revered classic remains as relevant as ever, providing the latest information in Francis D.K. Ching's signature style. Its rich and comprehensive approach clearly presents all of the basic concepts underlying building construction"--